Development of Nanozyme-Labeled Biomimetic Immunoassay for Determination of Sulfadiazine Residue in Foods - Jingbo He; Li Zhang; Longhua Xu; Feifan Kong; Zhixiang Xu (Advances in Polymer Technology)
The excessive use and ingestion of residues of sulfonamides harm the human body and the environment. To meet the requirements of the maximum residue limit specified by the Ministry of Agriculture of China, a rapid detection method urgently needs to be developed. In the present study, a molecularly imprinted polymer (MIP) that could selectively recognize sulfadiazine (SDZ) was prepared using SDZ as the template molecule and methacrylic acid as the functional monomer. Using MIP as biomimetic antibody and Au@Pt@SiO2 nanozyme as a marker, a new biomimetic immunoassay was developed to detect sulfadiazine. Under the optimal conditions, the limit of detection (IC15) and sensitivity (IC50) of this method were 0.09 and 6.1 mg/L, respectively. To determine the accuracy of this method, honey and milk samples spiked with sulfadiazine were analyzed, with recoveries in the range of 70.8%-90.2%. The method was also used for the quantitative analysis of sulfadiazine residues in milk powder and milk samples, producing results which correlated well with those obtained by high-performance liquid chromatography.